Profil Pembelajaran Akademik Mahasiswa Pada Matakuliah Fisiologi Tumbuhan di Masa Pandemi COVID - 19: (Academic Learning Profile of Students in Plant Physiology Course in The Covid – 19 Pandemic) - Ranti An Nisaa; Devi Anugrah (BIODIK, 2023)
To prevent the spread of COVID-19, students around the world cannot go to college. However, education must continue. Likewise, online plant physiology lectures take place. Researchers are interested in describing the internal factors of students that can influence students in mastering the material in plant physiology lectures during a pandemic. This quantitative descriptive research was conducted on biology education study program students who have taken Plant Physiology lectures in the 2020-2021 Academic Year. A total of 56 respondents were given a questionnaire related to their experiences during online lectures. The academic learning profile is based on students' internal aspects which include attention, memory, visual motor perception, thinking, and language. The profile of attention is that students can still focus on listening to lectures even though the camera in the zoom meeting is turned off (69.9%); memory, namely students can remember and re-explain the practicum steps that have been implemented (58.9%); visual motor perception, students can operate various application technologies used by lecturers during online lectures (60.7%); thinking, students can explain the results of the practicum that has been done (67.9%); and language, students can socialize when coordinating in group assignments (75%). Students can still attend lectures well even from their homes, are familiar with various learning applications, and can still communicate smoothly with their classmates. Key words: profile, plant physiology, online lecture, learning, COVID-19 ABSTRAK Untuk mencegah penyebaran COVID – 19, seluruh mahasiswa di seluruh dunia tidak dapat berkuliah. Namun perkuliahan harus tetap berjalan. Begitu pula perkuliahan matakuliah fisiologi tumbuhan yang berlangsung secara daring. Peneliti tertarik untuk mendeskripsikan faktor internal dari mahasiswa yang dapat mempengaruhi mahasiswa dalam penguasaan materi pada perkuliahan fisiologi tumbuhan selama masa pandemic. Penelitian deskriptif kuantitatif ini dilakukan pada mahasiswa program studi pendidikan biologi yang telah menempuh perkuliahan Fisiologi Tumbuhan pada Tahun Akademik 2020-2021. Sebanyak 56 responden diberikan kuesioner terkait pengalaman dirinya selama mengikuti perkuliahan daring. Profil pembelajaran akademik berdasarkan aspek internal mahasiswa yang meliputi attention, memory, persepsi visual motorik, thinking, dan language. Profil dari attention yakni mahasiswa tetap bisa fokus dalam menyimak perkuliahan walau kamera pada zoom meeting dimatikan (69,9%); memory yakni mahasiswa mampu mengingat dan menjelaskan ulang langkah-langkah praktikum yang sudah dilaksanakan (58,9%); persepsi visual motorik, mahasiswa mampu mengoperasikan berbagai teknologi aplikasi yang digunakan dosen selama perkuliahan daring (60,7%); thinking, mahasiswa mampu menjelaskan hasil praktikum yang telah dilakukan (67,9%); dan language, mahasiswa mampu bersosialisasi saat koordinasi dalam pengerjaan tugas kelompok (75%). Selama perkuliahan daring mahasiswa tetap dapat mengikuti perkuliahan dengan baik walau dari rumah masing-masing, sudah terbiasa dengan berbagai aplikasi pembelajaran, dan tetap dapat berkomunikasi lancar dengan teman sekelasnya. Kata kunci: profil, fisiologi tumbuhan, kuliah online, pembelajaran, COVID-19